EFEKTIVITAS PELATIHAN RESUSITASI JANTUNG PARU (RJP) BERBASIS SIMULASI TERHADAP KEMAUAN MELAKUKAN RJP PADA SISWA SEKOLAH MENENGAH ATAS - Abdul Qodir; Angernani Trias W; Dwi Soelistyoningsih (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIKes Panti Waluya Malang, 2026)
Background: Out-of-hospital cardiac arrest (OHCA) remains a major global public health challenge, with persistently low rates of bystander cardiopulmonary resuscitation (CPR). Limited willingness to perform CPR among bystanders has been identified as a key barrier to timely intervention, highlighting the need for effective training strategies to enhance individuals’ willingness to provide life-saving assistance during cardiac arrest emergencies Purpose: To analyze the effectiveness of simulation-based CPR training in improving the willingness of high school students to perform CPR Methods: A quasi-experimental one-group pretest–posttest design was conducted among 77 students selected using consecutive sampling. The intervention consisted of CPR training, including theoretical instruction and scenario-based simulation. The CPR willingness questionnaire comprised 10 items developed based on previous studies and had been tested for validity and reliability. Bivariate statistical analysis was performed using paired t-test/Wilcoxon test Result: Simulation-based cardiopulmonary resuscitation (CPR) training significantly improved high school students’ willingness to perform CPR, with the mean willingness score increasing from 36.20 to 39.51 (p < 0.01). Implication: CPR training effectively enhances students’ willingness to perform CPR. Therefore, the systematic integration of CPR training into school curricula through scenario-based learning approaches has the potential to increase bystander CPR rates. Nurses play a crucial role as educators and facilitators in the delivery of CPR training programs, while periodic retraining is necessary to sustain students’ readiness and willingness to respond to cardiac arrest emergencies over time Keywords: Cardiopulmonary resuscitation; Cardiac arrest, Willingness to perform CPR